Draft Annual Plan 1985-86 Volume I Statement of Figures Tamil Nadu - Planning Commission (Planning Commission, 1985)
The Annual Plan for 1985-86, the first year of the Seventh Five-Year Plan, has been formulated keeping in view the overall objectives and the policy and programme thrust set out in the approach document of the Union Planning Commission. the directions given in the framework for the Seventh Plan by the Working Groups constituted by the State Planning Commission have also been taken note of.
State Planning Commission, Tamil Nadu